The effect of excess beta-chain synthesis on cell-surface expression of allele-mismatched class II heterodimers in vivo. - Gilfillan, S (1990)
We have recently described 12 lines of H-2s/s mice carrying from 1 to 65 copies of an A beta k transgene. The transgene was coexpressed with the endogenous allele, and A beta K mRNA expression correlated well with transgene copy number. Overexpression of the transgene was associated with a variety of defects, including a significant reduction in I-A cell-surface expression. In this paper, we assess the effect of increased levels of A beta k mRNA synthesis on I-A cell-surface expression in these mice. Crossing representatives from several lines of A beta k mice to A alpha k transgenic mice demonstrated that the A beta k mRNA was translated and expressed at high levels on the cell surface in association with A alpha k. In H-2s/s (A alpha s /A beta s) mice carrying greater than 10 copies of the A beta k transgene, excess A beta k mRNA and protein synthesis did drive cell-surface expression of the less favored A alpha s/A beta k heterodimers. However, the highest levels of A beta k detected on the cell surface were only 50-70% of those observed in [B10.A(4R) x nontransgenic]F1 controls. Maximum levels of A alpha s/A beta k cell-surface expression were accompanied by a significant reduction in A alpha s/A beta s expression. Unpaired and improperly paired complexes were not detected intracellularly and appeared to be degraded quite rapidly. Thus, only a fraction of the chains competing for pairing reached the cell surface under conditions of asymmetric chain synthesis in these mice. This markedly reduced total Ia cell-surface levels in mice carrying greater than 10 copies of the A beta k transgene.